Efficacy of Fractional CO2 Laser in the Treatment of Macular Amyloidosis (Latakia University Journal -Medical Sciences Series, 2020)
Background: Macular amyloidosis is considered a common cutaneous disease, and cosmetic disorder. It's an unpleasant for patients especially when accompanied by sever itching. Despite the presence of various therapeutic modalities, none is considered curative or satisfactory, in addition to their side effects.Objective: Evaluate effectiveness of fractional co2 laser in the treatment of macular amyloidosis.Patients and Methods: Before & After Study (prospective) was conducted on 35 female patients with macular amyloidosis were treated with 4 sessions of fractional co2 laser with 4 weeks interval, followed by topical corticosteroid under occlusion for 24 hours (Betamethasone Valerate 0.1%). Treatment energy parameters have been remained constant in all sessions (15 watts). Improvement was evaluated using color grading scale before the first session and one month after the last session. We also evaluate degree of itching on scale from 0 to 10. In addition to evaluate resulting side effects after every session. Recurrence was reported as well, during the follow up period (three months after the last session).